Finite element analysis of abdominal aortic aneurysm using hyperelastic model - Danao, Louis Angelo M (2006)
Abdominal aortic aneurysm (AAA) rupture is the 12th leading cause of death in the United States with a rank comparable to HIV/AIDS with deaths exceeding 12,000 a year. These deaths are preventable with early detection and elective repair. The current criterion for elective repair is an aneurysm with maximum diameter of 5.5 cm. But almost 25% of ruptures are less than or equal to 5 cm making the criterion an unreliable predictor of rupture. From a biomechanical perspective, the best indicator of rupture is wall stress when the mechanical stress induced exceeds the tensile strength of the tissue. It is therefore necessary to accurately model the aneurysm non-invasively to estimate the in-vivo wall stress distribution. One clinical case of AAA was the subject of this study. A published hyperelastic strain energy function was used as the material model for the AAA wall. Data from spiral computed tomography (CT) scans were used as a means of reconstructing the 3D geometry of the AAA. Using finite element method, the stress distribution on the aortic wall under systolic pressure was determined and studied. Wall stress was complexly distributed on the surface of the AAA, with distinct regions of high and low stress. Peak wall stress was found to be 0.55 MPa, located at the anterior portion of the AAA. The application of hyperelasticity to finite element analysis of AAA provides a starting foundation to the development of more accurate simulations. A map with von Mises stress (0.65 MPa) failure line indicating the failure zone plotted on pressure versus thickness charts is a possible replacement to the single critical diameter criterion. This plot will be specific to a family of AAA with maximum diameters falling within a particular range. The end product is a clinical tool that will give better diagnosis of AAA rupture risk based on maximum probable stress but will present equal convenience of use as the 5.5 cm critical diameter criterion.